2000
DOI: 10.1538/expanim.49.197
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Age-Related Changes in Cytochrome P450 Expression in APA Hamster Livers.

Abstract: Abstract:To establish the baseline data, age-related changes and the regional expression of the hepatic P450 isozymes in Syrian hamsters of the APA strain at 3, 6, 12, 18 months old were examined by immunological techniques. Immunohistochemical analysis of liver serial sections revealed that the midzonal and perivenous regions (zones 2 and 3, respectively) were stained with the anti-rat CYP1A1/2, 2B1/2 and 2E1 antibodies. These three antibodies most intensely stained the hepatocytes around the central vein. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Here, hepatocytes are non-uniform in their positions and cellular functions. This approach can be used for drug testing and analyzing the effect of hepatic metabolism with age [23] and metabolic diseases in vivo. Our methodlogy may provide additional information in understanding hepatobiliary zonal metabolism when in mouse models of different pathological conditions, and provide valuable insights in clinical medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Here, hepatocytes are non-uniform in their positions and cellular functions. This approach can be used for drug testing and analyzing the effect of hepatic metabolism with age [23] and metabolic diseases in vivo. Our methodlogy may provide additional information in understanding hepatobiliary zonal metabolism when in mouse models of different pathological conditions, and provide valuable insights in clinical medicine.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that APA hamsters of SZ3M have developed a renal disorder [34,37], because experimental renal failure has been reported to change drugmetabolizing activity and P450 content in rats [60]. Otherwise, we have reported that the expression levels of most P450 isozymes have their peaks at 6 months of age [6], which corresponds to the age of APA hamsters of SZ3M. The increased level of P450 expression may make the SZ-induced changes of P450 expression level obscure, but further studies are needed to find the cause of these phenomena.…”
Section: Discussionmentioning
confidence: 91%
“…To easily understand the localization of P450 isozymes, we referred to the method of Bühler [8] and defined the liver acinus as having three zones: the periportal region (zone 1), the midzonal region of the acinus (zone 2), and the perivenous region (zone 3) which contains a few cell layers in the periphery of the central vein (pcv) [6].…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation